Two Paradigms of Aesthetics in Haskalah Literary Criticism: From Satanov to Lebensohn - Banbaji, Amir (Hebrew studies, 2012)
Focusing on aesthetic insights, penned by key figures of Haskalah letters, this article argues that Haskalah literary theory and aesthetics develop in two distinct philosophical lines of thought. It is further argued that distinguishing between these lines and considering their relative weight is crucial for understanding the maskilim's relationship to the sacred Jewish textual tradition and to the European enlightenment. The first path noted in the paper has already been acknowledged by historians of Hebrew aesthetic thought. Haskalah thinkers like Isaac Euchel, Joel Bril, and others, believed that Modern Hebrew aesthetics should universalize Hebrew literary expression. They emphasized the transformative communicative acts that Modern Hebrew literature can accomplish in the emerging public sphere., The competing aesthetic insight investigated and highlighted in this article has been pursued by Isaac Satanov and Abraham D. Lebenshon. Attempting to promote a cryptic, esoteric and elitist notion of literary experience, both thinkers argued, contrary to the dominant view, that the modern realm of beauty and aesthetic experience must retain the traditional role of hiding and isolating wisdom from the general public. The paper argues that Satanov and Lebensohn's contrarian view of the relation between beauty and truth significantly modifies our understanding of the secular situation of Modern Hebrew literature.